Pentingnya Proses Verifikasi Kesesuaian Data Koordinat Lokasi Pada Proses Registrasi Dan Verifikasi Data Untuk Permohonan NOTAM - Manggala, Darma; Amir, Elfi; Sidik, Syahril (Jurnal Bisnis dan Operasi Penerbangan, 2025)
NOTAM is a notice disseminated by telecommunication that contains information about the establishment, condition, or change of facilities, services, procedures, or flight hazards, which must be known in a timely manner by personnel related to flight operations, at the airport itself NOTAM is issued by the NOTAM Office through the Regional Aeronautical Information Service. The research method used is a qualitative research method in which the researcher studies how the group works in actual conditions through observation and interviews. There are various types of information published through NOTAM, one of which is information about airspace or Airspcae. The verification process is included in the registration process, the process of which is regulated in SOP 02 (procedure for registration and verification of requests for changes to the addition of aeronautical information in the PIA region). When verifying NOTAM applications related to airspace or Airspace Reservation, there is no mechanism for verifying the suitability of location coordinates. Therefore, it is important to include technical guidance related to verification of location coordinates.